The Effect of Company Size, Earning Per Share, Price to Book Value, and Exchange Rate on Stock Returns - Pambudi, Bhakti Setya; Sukesti, Fatmawati; Kristiana, Ida (Economics and Business International Conference Proceeding, 2024)
This study aims to examine the influence of company size, earning per share, price to book value, and exchange rate on stock returns. This type of research is quantitative research. The sample in this study was obtained using the purposive sampling method, which is the selection of samples with predetermined criteria. Based on the purposive sampling method, 34 samples were obtained from 57 property and real estate companies listed on the IDX for the 2018 - 2022 period. The analysis technique used is multiple linear regression. The results of the data analysis showed that the test of the Company Size hypothesis had a negative effect on stock returns, Earning Per Share had a positive and significant effect on stock returns, Price To Book Value had no positive effect, Exchange Rate had a negative effect on stock returns. simultaneously Company Size, Earning Per Share, Price To Book Value and Exchange Rate has a positive and significant effect on stock returns.